2010
DOI: 10.1099/mic.0.036178-0
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the xenobiotic organic disulphide 4,4′-dithiodibutyric acid by Rhodococcus erythropolis strain MI2 and comparison with the microbial utilization of 3,3′-dithiodipropionic acid and 3,3′-thiodipropionic acid

Abstract: Application of the non-toxic 3,3′-thiodipropionic acid (TDP) and 3,3′-dithiodipropionic acid (DTDP) as precursors for the microbial production of polythioesters (PTEs), a class of biologically persistent biopolymers containing sulphur in the backbone, was successfully established previously. However, synthesis of PTEs containing 4-mercaptobutyrate (4MB) as building blocks could not be achieved. The very harmful 4MB is not used as a PTE precursor or as the carbon source for growth by any known strain. As a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…3A). As also described by Wüb-beler et al (17), a considerable amount of 4-oxo-4-sulfanylbutyric acid was detected in the culture supernatants of the wild type and the transposon-induced mutants (Fig. 3B).…”
Section: Dtdb Degradation Intermediatessupporting
confidence: 51%
See 2 more Smart Citations
“…3A). As also described by Wüb-beler et al (17), a considerable amount of 4-oxo-4-sulfanylbutyric acid was detected in the culture supernatants of the wild type and the transposon-induced mutants (Fig. 3B).…”
Section: Dtdb Degradation Intermediatessupporting
confidence: 51%
“…According to the DTDB degradation pathway proposed previously (17) (Fig. 1), the initial step is the reduction of the disulfide bond, resulting in the formation of two 4MB molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, little is known about bacterial enzymes involved in 3-MPA metabolism. Strains from the Pseudomonas family are capable of 3-MPA utilization (28). Conversion of 3-SPA to 3-sulfinopropionyl-CoA in Proteobacteria has been attributed to succinylCoA synthetase, (44,45); however, enzymatic oxidation of 3-MPA to 3-SPA remains to be identified.…”
mentioning
confidence: 99%
“…Later, other investigators showed the participation of the SucCD of Advenella mimigardefordensis DPN7 T in the degradation pathway of 3,3=-dithiodipropionic acid (DTDP), a precursor for the production of polythioesters in bacteria (25)(26)(27)(28). In this strain, DTDP is metabolized via the intermediate product 3-sulfinopropionate (3SP) (29)(30)(31).…”
mentioning
confidence: 99%